Two of the field researchers, Margaret Brock and RLJ, empty out Camp Finney's makeshift washroom - Bazely, Dawn (1982)
Two of the field researchers at Camp Finney taking out the camp's makeshift washroom in the metal container with a wooden plank while trudging through high vegetation